Evaluation of Diplopia by Emergency Medicine Physicians and Consulting Neurologists. Issue 1 (March 2022) - Feng, Yilin; Commiskey, Patrick W.; Deveney, Tatiana K.; De Lott, Lindsey B.; Trobe, Jonathan D.
Abstract : Background: Appropriate evaluation of diplopia requires separating serious from benign causes. If providers are not adept in this task, diagnosis of critical conditions may be delayed and unnecessary testing may result. Methods: We studied the records of 100 consecutive patients who presented to an emergency department between 2010 and 2020 with diplopia as a prominent symptom. We rated the performance of emergency medicine physicians (EMPs) and consulting neurologists (CNs) in the examination, diagnosis, and ordering of diagnostic tests according to standards based on neuro-ophthalmologic consultation and the neuro-ophthalmologic literature. Results: EMPs made no diagnosis or an incorrect diagnosis in 88 (88%) of 100 encounters. They ordered 14 unindicated and 12 incorrect studies, mostly noncontrast computed tomography scans. CNs made an incorrect diagnosis in 13 (31%) encounters. They ordered 6 unindicated and 2 incorrect studies. The total charge for unindicated and incorrect studies ordered by EMPs and CNs was 119, 950. Conclusions: EMPs and CNs made frequent errors in the examination, diagnosis, and ordering of diagnostic studies, leading to inefficient care and unnecessary testing. EMPs largely delegated the evaluation of diplopia to their consultants. If such consultative support were not available, the care of diplopic patients would be delayed. CNs performed more complete examinations, but rarely enough to allow appreciation of the pattern of ocular misalignment, contributing to misdiagnoses and ordering errors. The identification of these provider errors allows for more targeted teaching in the evaluation of diplopia. Abstract : Supplemental Digital Content is Available in the Text.